Symbolic Interaction Analysis of The Baayun Maulid Tradition of The Banjar Community - Arif Sugian; Ady Muh. Zainul Mustofa (Indonesian Journal of Islamic Education and Local Culture, 2023)
The Baayun Maulid tradition is a religious celebration specifically practised by the Banjar community in the month of Rabi'ul Awwal or what is commonly referred to as the "month of mulud". It is usually centred in the mosque in conjunction with the commemoration of the maulid of the prophet Muhammad. Children are swung on swings by their parents, the verses of the Holy Qur'an are recited, the verses of the prophet's maulid are chanted and prayers are offered to them. This research uses a qualitative approach with a focus on understanding and interpreting the symbols involved in every aspect of the Baayun Maulid tradition. The research method used was content analysis of documentation related to the Baayun Maulid tradition. The results show that symbolic interaction in this tradition covers a variety of elements, including celebration procedures, the use of religious symbols, and community participation in various ritual activities. The symbols found in this tradition not only contain religious values, but also reflect the values of close social solidarity and deep cultural identity among the Banjar people. The Baayun Maulid tradition is not only a religious ceremony, but is also recognised as an effective means to strengthen social ties within a community. Religious symbols become the glue that connects individuals within a framework of togetherness and unity. As such, this paper contributes to further understanding of how symbols in religious traditions can shape and strengthen a community's cultural identity